2022
DOI: 10.1111/ctr.14864
|View full text |Cite
|
Sign up to set email alerts
|

Influence of donor and recipient sex on outcomes following simultaneous pancreas–kidney transplantation in the new millennium: Single‐center experience and review of the literature

Abstract: Introduction:The influence of sex on outcomes following simultaneous pancreaskidney transplantation (SPKT) in the modern era is uncertain. Methods: We retrospectively studied 255 patients undergoing SPKT from 11/2001 to 8/2020. Cases were stratified according to donor (D) sex, recipient (R) sex, 4 D/R sex categories, and D/R sex-matched versus mismatched.Results: D-male was associated with slightly higher patient (p = .08) and kidney (p = .002) but not pancreas (p = .23) graft survival rates (GSR) compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…On the other hand, female gender was protective for the incidence of SCP. This is interesting, as previous data failed to show a relevant impact of recipient gender on outcome after SPK [38,39]. Importantly, we found no association between SCP and donor age, recipient age, or the duration of cold ischemia in this cohort.…”
Section: Discussionsupporting
confidence: 50%
“…On the other hand, female gender was protective for the incidence of SCP. This is interesting, as previous data failed to show a relevant impact of recipient gender on outcome after SPK [38,39]. Importantly, we found no association between SCP and donor age, recipient age, or the duration of cold ischemia in this cohort.…”
Section: Discussionsupporting
confidence: 50%
“…Participants were stratified according to donor (D) sex, recipient (R) sex, 4 D/R sex categories, and D/R sex-matched vs mismatched groups. 18 This study found that D-male patients had a higher kidney graft survival ( P = .002) and patient survival rate ( P = .08) compared to the D-female patients. There was no difference in pancreas graft survival between the D-male and D-female groups ( P = .23).…”
Section: Pancreatic Transplantationmentioning
confidence: 60%
“…Overall, the D-female groups demonstrated a higher risk of kidney graft failure (HR 2.12, 1.26-3.57, P = .005), regardless of recipient sex. Survival rates appear higher in the D-male/R-male categories and lower in D-female/R-male categories, 18 but more work needs to be done to corroborate these findings.…”
Section: Pancreatic Transplantationmentioning
confidence: 97%
“…Our study showed that a female recipient had an increased baseline of systemic arterial and renal venous D-loop. Several studies have demonstrated that biological sex differences between donor and recipient impacts graft outcome [27][28][29]. In addition, it is known that, in general, women have significantly higher mitochondria-related biomarkers, such as respiration and ATP-content, which has been demonstrated in multiple organs and study models [30,31].…”
Section: Discussionmentioning
confidence: 99%